PENGARUH PROFITABILITAS, UKURAN DEWAN KOMISARIS, UKURAN DEWAN PENGAWAS SYARIAH, UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA BANK UMUM SYARIAH DI INDONESIA (PERIODE 2012-2016) - Dahlia Mamik Kholifah, 13.05.52.0003; Aini, Nur (Students Journal of Accounting and Banking, 2018)
This study examines and analyzes the influence of Profitability, Size of Board of Commissioners, Size of Sharia Supervisory Board, Company Size on Islamic Social Reporting Disclosure. The population in this study is a Sharia Bank registered in Bank Indonesia supervised by OJK 2012-2016. Sampling method using purposive sampling with period of research year 2012 until 2016. Influence between variable is explained by using method of multiple linear regression analysis. The results of this study indicate that the profitability and the size of the sharia supervisory board have no effect on the ISR disclosure, while the size of the board of commissioners and firm size has a significant positive effect on the ISR disclosure.Keywords: Disclosure of Islamic Social Reporting (ISR), Profitability, Board of Commissioner Size, Sharia Supervisory Board Size, Company Size